SISTEM INFORMASI PENDATAAN ANAK PANTI ASUHAN “RIANG” BERBASIS WEBSITE - Menhya Snae (P3M- Politeknik Negeri Kupang, 2020)
Abstract Childcare Social Institution is a social welfare business institution that has the responsibility to provide social welfare services to neglected children by carrying out assistance and alleviation of neglected children, providing replacement services for parents / guardians of children in fulfilling physical, mental and social needs to foster children so as to obtain broad, appropriate and adequate opportunity for the development of his personality as expected as part of the future generation of the nation's ideals and as people who will actively participate in the field of national development. Data collection on orphanage children that are not properly implemented is one of the obstacles in checking the number of orphanage children who have not been in homes and who are still in the institution, with education levels, origin, how long they are in the orphanage and various information related to children House. The problem is how to design and build a system for collecting orphanage children. With the aim of building a website-based orphanage data collection information system. Which is useful for facilitating access to orphanage data, archiving data on orphanages that are more efficient, facilitating the processing of orphanage data. The results of this study are an information system for data collection of website-based